2016
DOI: 10.1136/bmjdrc-2015-000148
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D for the treatment of painful diabetic neuropathy

Abstract: ObjectiveTo assess the effect of high-dose vitamin D in patients with painful diabetic neuropathy.MethodsA single intramuscular dose of 600 000 IU vitamin D was administered, and the effects on metabolic parameters and neuropathic pain assessed over 20 weeks.Results143 participants with predominantly type 2 diabetes, aged 52.31±11.48 years, with a Douleur Neuropathique 4 (DN4) score (3.0±1.8), total McGill pain score (21.2±14.9), and Short Form McGill Pain Questionnaire (SFMPQ) score (2.1±0.9), were enrolled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 39 publications
2
70
1
10
Order By: Relevance
“…In this study, we investigated the relationship between vitamin D and DPN at different ages. The results showed that vitamin D was only associated with DPN in the elderly patients but not in young and [18][19][20] but not to improve blood glucose 21 and endothelial function. 22 Schwann cells are peripheral glial cells that synthesize and secrete various growth factors, such as nerve growth factor (NGF), insulinlike growth factor (IGF), ciliary neurotrophic factor (CNTF), and neurotrophin-3 (NT-3), and these growth factors play an important role in nerve damage and repair.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we investigated the relationship between vitamin D and DPN at different ages. The results showed that vitamin D was only associated with DPN in the elderly patients but not in young and [18][19][20] but not to improve blood glucose 21 and endothelial function. 22 Schwann cells are peripheral glial cells that synthesize and secrete various growth factors, such as nerve growth factor (NGF), insulinlike growth factor (IGF), ciliary neurotrophic factor (CNTF), and neurotrophin-3 (NT-3), and these growth factors play an important role in nerve damage and repair.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the mechanism involved, vitamin D deficiency can affect glucose metabolism by impairing islet β‐cell function, reduce neurotrophic factors causing neurological dysfunction, and attenuate anti‐inflammatory effects leading to vascular endothelial dysfunction and supporting the development of atherosclerosis, thereby promoting the occurrence and development of DPN . However, studies on vitamin D supplementation for DPN have been shown to improve DPN neuropathic pain and affect DPN development by repairing and protecting nerves but not to improve blood glucose and endothelial function …”
Section: Discussionmentioning
confidence: 99%
“…In addition, most studies did not differentiate between painful-DPN and painless-DPN [23]. There is some evidence, although not consistent, that vitamin D supplementation improves painful neuropathic symptoms [24], suggesting that vitamin D may have a role in the pathogenesis of painful-DPN. Our study was designed to address these limitations by: (1) careful characterization and detailed phenotyping of DPN, using internationally recognized standards; (2) restricting the collection of vitamin D blood samples to during the summer months (July to September); (3) quantifying sunlight exposure and activity levels, using validated questionnaires to estimate exposure to UV radiation; and (4) examining the relationship of vitamin D with measures of small and large nerve fibre function using quantitative sensory testing, skin biopsy and nerve conduction studies.…”
Section: Discussionmentioning
confidence: 97%
“…Proinflammatory cytokines are thought to play a role in the pathogenesis of diabetic neuropathy, and 25‐hydroxyvitamin D may regulate inflammatory mediators interleukin‐13 (IL‐13) and IL‐17 in diabetes and diabetic neuropathy, suggesting that vitamin D deficiency may be a modifiable risk factor . One nonrandomized and 2 open‐label trials demonstrated that treatment with vitamin D 3 improved pain levels in patients with diabetic neuropathy . In addition, patients with vitamin D deficiency and myeloma receiving bortezomib and/or thalidomide were more likely to develop severe peripheral neuropathy than those patients with normal vitamin D levels (see Table S1 online).…”
Section: Dietary Supplementsmentioning
confidence: 99%